Population‐level thermal performance of a cold‐water ectotherm is linked to ontogeny and local environmental heterogeneity. (15th July 2013) - Hossack, Blake R.; Lowe, Winsor H.; Webb, Molly A. H.; Talbott, Mariah J.; Kappenman, Kevin M.; Corn, Paul Stephen
Summary Negative effects of global warming are predicted to be most severe for species that occupy a narrow range of temperatures, have limited dispersal abilities or have long generation times. These are characteristics typical of many species that occupy small, cold streams. Habitat use, vulnerabilities and mechanisms for coping with local conditions can differ among populations and ontogenetically within populations, potentially affecting species‐level responses to climate change. However, we still have little knowledge of mean thermal performance for many vertebrates, let alone variation in performance among populations. Assessment of these sources of variation in thermal performance is critical for projecting the effects of climate change on species and for identifying management strategies to ameliorate its effects. To gauge how populations of the Rocky Mountain tailed frog (Ascaphus montanus) might respond to long‐term effects of climate change, we measured the ability of tadpoles from six populations in Glacier National Park (Montana, U.S.A.) to acclimate to a range of temperatures. We compared survival among populations according to tadpole age (1 year or 2 years) and according to the mean and variance of late‐summer temperatures in natal streams. The ability of tadpoles to acclimate to warm temperatures increased with age and with variance in late‐summer temperature of natal streams. Moreover, performance differed among populations from the same catchment. Our experiments with a cold‐water species show that population‐level performance varies across small geographic scales and is linked to local environmental heterogeneity. This variation could influence the rate and mode of species‐level responses to climate change, both by facilitating local persistence in the face of changes in thermal conditions and by providing thermally tolerant colonists to neighbouring populations.